PIEZO1 drives trophoblast fusion and placental development - Yang Zhang; Ke Z. Shan; Pengfei Liang; Augustus J. Lowry; Liping Feng; Huanghe Yang (Nature Communications)
Abstract PIEZO1, a mechanosensor in endothelial cells, plays a critical role in fetal vascular development during embryogenesis. However, its expression and function in placental trophoblasts remain unexplored. Here, we demonstrate that PIEZO1 is expressed in placental villus trophoblasts, where it is essential for trophoblast fusion and placental development. Mice with trophoblast-specific PIEZO1 knockout exhibit embryonic lethality without obvious vascular defects. Instead, PIEZO1 deficiency disrupts the formation of the syncytiotrophoblast layer in the placenta. Mechanistically, PIEZO1-mediated calcium influx activates TMEM16F lipid scramblase, facilitating the externalization of phosphatidylserine, a key “fuse-me” signal for trophoblast fusion. These findings reveal PIEZO1 as a crucial mechanosensor in trophoblasts and highlight its essential role in regulating trophoblast fusion and placental development, expanding our understanding of PIEZO1’s functions beyond endothelial cells during pregnancy.